THE TOMORROW OF ENGINEERING: HOW AI, ROBOTICS, AND GREEN TECHNOLOGIES ARE SHAPING THE ENGINEERING - Diyorbek Norqulov (World Scientific Research Journal, 2025)
The engineering landscape is undergoing a profound transformation driven by the convergence of artificial intelligence (AI), robotics, and green technologies—a fusion that is redefining the scope and impact of mechanical engineering. This article presents a forward-looking analysis of emerging trends in intelligent systems, automated machinery, and sustainable mechanical design, with a particular focus on how these forces are reshaping the profession globally.